Biosorption of BF-4B Reactive Red Dye by using Leaves of Macrophytes Eichhornia crassipes - Aparecido Nivaldo Módenes; Andreine Aline Ross; Bruna Vanessa Souza; Juliana Dotto; Claudinéia Queli Geraldi; Fernando Rodolfo Espinoza-Quiñones; Alexander Dimitrov Kroumov (International Journal Bioautomation, 2013)
The removal potential on BF-4B reactive red dye by Eichhornia crassipes dried leaves has been investigated. Furthermore, the influence of process parameters such as solution pH, agitation, and particle size on the dye adsorption efficiency was assessed. Both kinetic and equilibrium experiments were performed in batch operation of the system. Kinetic results demonstrated that the equilibrium state was achieved after 45 min process time. The kinetic experimental data were best described by applying a pseudo-second order model that evaluated the value of rate constant 0.22 g/mg/min and an equilibrium dye concentration 8.20 mg/g. A set of isotherm models, taken from knowledge database, was tested in order to represent the equilibrium adsorption data. The Langmuir model performed the best when fitting experimental data where the maximum adsorption capacity of 20.38 mg/g was achieved. The results demonstrated that the E. crassipes has good potential to be used as a biosorbent in industrial treatment systems to remove reactive dyes from textile effluents.